Optimisation of robotised sealing stations in paint shops by process simulation and automatic path planning. (1st January 2014) - Mark, Andreas; Bohlin, Robert; Segerdahl, Daniel; Edelvik, Fredrik; Carlson, Johan S.
Application of sealing materials is done in order to prevent water leakage into cavities of the car body, and to reduce noise. The complexity of the sealing spray process is characterised by multi-phase and free surface flows, multi-scale phenomena, and large moving geometries, which poses great challenges for mathematical modelling and simulation. The aim of this paper is to present a novel framework that includes detailed process simulation and automatic generation of collision free robot paths. To verify the simulations, the resulting width, thickness and shape of applied material on test plates as a function of time and spraying distance have been compared to experiments. The agreement is in general very good. The efficient implementation makes it possible to simulate application of one meter of sealing material in less than an hour on a standard computer, and it is therefore feasible to include such detailed simulations in the production preparation process and off-line programming of the sealing robots.